Behavior of Coliphage Lambda in Shigella flexneri 2a - Gemski, P. (1972)
The insensitivity of wild-type Shigella flexneri 2a to coliphage λ is a consequence of its native genetic defect in the malA gene cluster. The “smooth” S. flexneri 2a lipopolysaccharide layer affects the efficient adsorption of λ. Derivatives, capable of serving as functional hosts for λ, were obtained by repairing the malA lesion, enabling the expression of the malB-λrcp region of S. flexneri. Introduction of a mutation into S. flexneri causing a “rough” lipopolysaccharide character resulted in more efficient adsorption of λ. Such S. flexneri hosts can be stably lysogenized and upon induction yield gal(+)-transducing lysates. Lambda propagated on a malA(+) rough S. flexneri host was restricted by Escherichia coli K-12 and E. coli B, but not by E. coli C. This S. flexneri host did not restrict λ grown on these E. coli strains.